Preclinical Studies on Convalescent Human Immune Plasma-Derived Exosome: Omics and Antiviral Properties to SARS-CoV-2 - Taşlı, Neslihan Pakize; Gönen, Zeynep Burçin; Kırbaş, Oğuz Kaan; Gökdemir, Nur Seda; Bozkurt, Batuhan Turhan; Bayrakcı, Buse; Sağraç, Derya; Taşkan, Ezgi; Demir, Sevda; Ekimci Gürcan, Nur; Bayındır Bilgiç, Melike; Bayrak, Ömer Faruk; et al. (Frontiers in Immunology, 2022)
The scale of the COVID-19 pandemic forced urgent measures for the development of new therapeutics. One of these strategies is the use of convalescent plasma (CP) as a conventional source for passive immunity. Recently, there has been interest in CP-derived exosomes. In this report, we present a structural, biochemical, and biological characterization of our proprietary product, convalescent human immune plasma-derived exosome (ChipEXO), following the guidelines set forth by the Turkish Ministry of Health and the Turkish Red Crescent, the Good Manufacturing Practice, the International Society for Extracellular Vesicles, and the Gene Ontology Consortium. The data support the safety and efficacy of this product against SARS-CoV-2 infections in preclinical models.